SOSIALISASI MODUL AJAR MATEMATIKA BERDIFERENSIASI BERBANTUAN GEOGEBRA PADA GURU SMANKO BENGKULU - Hanifah, Agus Susanta, Hari Sumardi, Fifie Novrianti (PT.JNDI, JURNAL BIMA, 2024)
The socialization of the geogebra-assisted differentiated mathematics teaching module to Bengkulu Sports Talent High School teachers has been carried out successfully. The participants consisted of: 2 mathematics teachers, 1 physics teacher, 6 students, and 10 mathematics teachers who were FKIP UNIB Mathematics Education Masters students taking the Mathematics Learning Tools Development course. Activities are carried out in the following order: 1) Introducing Differentiated Teaching Modules, 2) Introducing 21st Century Learning, 3) Introducing the APOS Model, 4) Introducing Geogebra, 5) Implementing the Linear Program teaching module based on the APOS Model with the help of Geogebra. 6) Give Likert scale response questionnaires to participating teachers and students at SMANKO Bengkulu. After the response questionnaire was processed using a Likert scale, the results were: 1) the mean score of teacher responses to the Linear Program teaching module was 92.27 in the very good category, and 2) the student response score to the Linear Program teaching module was 87.6 in the very good category. The average response score of training participants to the Linear Program teaching module was 89.93 and was in the very high category. The faces of teachers and students look happy when implementing the Linear Program teaching module. The Physics teacher said he would use Geogebra as a Physics learning tool.